Meniscal scaffold implantation in post meniscectomy syndrome results in clinical and radiological outcomes comparable to primary subtotal meniscectomy in patients without post meniscectomy syndrome - Maione, Alessio; Ricci, Martina; Perfetti, Sofia; Poggioli, Francesco; Calanna, Filippo; Puce, Marco; Usellini, Eva; Randelli, Pietro Simone; Berruto, Massimo (Acta Biomedica Atenei Parmensis, 2024)
Background and aim: The aim of the study was to assess clinical and radiological outcomes among patients who underwent scaffold implantation after post meniscectomy syndrome (scaffold group) comparing them with patients undergoing primary subtotal meniscectomy (primary subtotal meniscectomy group) without post meniscectomy syndrome at a minimum of 3 years of follow-up. Moreover, the morphology of the meniscal implant was verified by MRI at the last follow-up. Methods: 24 patients were enrolled (age, 37 ± 12.2 years) and two groups of 12 patients were created (scaffold and primary subtotal meniscectomy). Data were collected before surgery, at 12 months and at the last follow-up (min 3 years - max 13 years). Clinical and radiological outcomes (Subjective IKDC score, VAS, Tegner scale, physical examination, Kellgren-Lawrence classification) were collected. MRI images were analyzed according to the Genovese classification. Results: Both groups showed an improvement in knee function at the last follow-up. No differences were recorded in terms of pain reduction at 1 year, while subtotal meniscectomy showed a significantly lower VAS score at the last follow-up. Both groups showed a significant progression of knee osteoarthritis at the last follow-up. No patient showed a completely reabsorbed scaffold. Conclusions: The ActifitTM polyurethane implant demonstrated good clinical and radiological results in patients with symptomatic post meniscectomy syndrome at final follow-up. However IKDC score and VAS showed inferior clinical results compared to those of primary subtotal meniscectomy.